IS THERE A RELATIONSHIP BETWEEN VITAMIN D STATUS AND HYPOCALCEMIA AFTER TOTAL THYROIDECTOMY? - Dağlar, G. (Acta Endocrinol (Buchar), 2016)
CONTEXT: Vitamin D plays a crucial role in calcium metabolism through parathormone-dependent process. Deficiency of this important nutrient may be associated with hypocalcemia after thyroidectomy. OBJECTIVE: To evaluate the role of vitamin D in predicting hypocalcemia following total thyroidectomy. SUBJECTS AND METHODS: One hundred and fifty patients who underwent total thyroidectomy for benign or malignant thyroid disease were included in this prospective study. The association between preoperative vitamin D status and the development of hypocalcemia were investigated. RESULTS: Biochemical and symptomatic hypocalcemia were found in 28 (18.7%) and 22 (14.7%) patients, respectively. Preoperative vit D level was found significantly lower in patients with biochemical (p = 0.006) and clinical (p < 0.001) hypocalcemia in comparison to normocalcemic patients. The patients who had <10 ng/mL vit D level (severe deficiency) developed significantly more biochemical and clinical hypocalcemia than the patients with serum vit D level higher than 10 ng/mL (p = 0.030 and p < 0.001, respectively). CONCLUSIONS: Although postthyroidectomy hypocalcemia is multifactorial, vit D deficiency, particularly severe form, is significantly associated with the development of biochemical and clinical hypocalcemia. Vit D supplementation can prevent this unwanted complication in such patients.